Program Pemulihan Pariwisata Jembatan dan Wisata Mangrov Desa Niranusa Kecamatan Maurole Kabupaten Ende - Timba, Frederiksen Novenrius Sini; Bare, Yohanes (Universitas Nusantara PGRI Kediri, 2021)
Niranusa Village is one of the villages in the Ende Regency area that has beautiful natural conditions, one of which is a bridge and mangrove tourism. Niranusa Village has an interesting natural charm. In addition to having white sand beaches, in some parts of the beach in Niranusa has been overgrown by mangroves naturally. The concept of tourism that becomes potential in this village is ecotourism. The lotus storm that hit the East Nusa Tenggara and Abrasion areas also affected the coastal area of Niranusa Village causing damage to bridge ecotourism and mangrove tourism. The purpose of this activity is the process of breeding bridge ecotourism and mangrove tourism in Niranusa village. The process of restoring bridge ecotourism and mangrove tourism consists of planning, implementation and evaluation stages. The work carried out for 27 days restored tourism to around 80% of the target and overall it can be used as a tourist spot for Niranusa.